2016
DOI: 10.1016/j.ophtha.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Access to Eye Care in the Contiguous United States by Calculated Driving Time in the United States Medicare Population

Abstract: Purpose To quantify the proximity to eye care in the contiguous United States by calculating driving routes and driving time using a census-based approach. Design Cross-sectional study based on United States (US) census data, Medicare payment data, and OpenStreetMap. Participants 2010 US census survey respondents older than 65 years. Methods For each state in the United States, the addresses of all practicing ophthalmologists and optometrists were obtained from the 2012 Medicare Provider Utilization and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 10 publications
0
36
1
Order By: Relevance
“…TO THE EDITOR: Lee et al 1 state, "Our findings contrast with the results of Gibson, 2 who analyzed 3143 counties in the United States and found that 24.1% of the counties were in the lower 2 quartiles of ophthalmologist availability but in the upper 2 quartiles of optometrist availability." Gibson 2 created population-weighted quartiles of the county-level number of ophthalmologists per capita and the county-level number of optometrists per capita.…”
contrasting
confidence: 90%
See 1 more Smart Citation
“…TO THE EDITOR: Lee et al 1 state, "Our findings contrast with the results of Gibson, 2 who analyzed 3143 counties in the United States and found that 24.1% of the counties were in the lower 2 quartiles of ophthalmologist availability but in the upper 2 quartiles of optometrist availability." Gibson 2 created population-weighted quartiles of the county-level number of ophthalmologists per capita and the county-level number of optometrists per capita.…”
contrasting
confidence: 90%
“…Lee et al 1 maintain that "this method of analysis grossly underestimates availability." This letter argues that Lee et al 1 did not support these assertions and notes that it has not been established that driving time to the closest eye care provider, the measure of provider availability used by Lee et al, 1 is a better predictor of vision health outcomes than other measures of the availability of eye care providers.…”
mentioning
confidence: 97%
“…Lack of access to eye care providers has be attributed to workforce limitations and poor integration of optical services into existing eye care services. (7) While US eye care providers have been shown to be within reasonable drive times from patients’ homes,(27, 28) areas of the developing world have a great shortage of eye care providers who are often restricted to urban centers which limits accessibility. (7)…”
Section: Social Determinants Of Ure Correctionmentioning
confidence: 99%
“…5 Not surprisingly, the geographic distribution of ophthalmologists and optometrists is not uniform within states, which has led some observers to argue that regional access problems exist for the provision of some services and the performance of some procedures. 5,6 Over the last several years, some states have expanded optometric scope of practice, ostensibly to improve patients' access to eye care. Newly granted privileges include laser photocoagulation and photoablative procedures, intraocular injections, and eyelid surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…5 Data showing that these expanded privileges have improved patients' access to care is lacking and some recent studies have concluded that access to care has not changed in states such as Oklahoma that have allowed optometrists to perform laser procedures. 5,6,7,8 Additionally, data showing that expanded privileges have enabled patients with more advanced eye diseases and higher risks of vision loss to increasingly obtain care from optometrists is also lacking. To better guide those state legislatures that are considering expanding privileges of optometrists and other non-ophthalmologists, it is critical to understand the characteristics of patients who seek care from ophthalmologists and optometrists.…”
Section: Introductionmentioning
confidence: 99%